Metal-phenolic-network-coated gold nanoclusters for enhanced photothermal/chemodynamic/immunogenic cancer therapy - Tingyu Yang; Liqun Dai; Jie Liu; Yi Lu; Meng Pan; Lili Pan; Lin Ye; Liping Yuan; Xicheng Li; Zhongwu Bei; Zhiyong Qian (Bioactive Materials)
Triple-negative breast cancer (TNBC) is the most aggressive subtype of breast cancer, characterised by a short survival period, high malignancy, strong invasiveness, and high rates of recurrence and metastasis. Due to its unique molecular phenotype, TNBC is insensitive to endocrine therapy or molecular targeted therapy. The conventional treatment approach involves systemic chemotherapy for overall management; however, adjuvant chemotherapy after surgery has shown poor efficacy as residual lesions can easily lead to tumour recurrence. Therefore, there is an urgent need to find more effective treatment strategies. Herein, we designed a gold nanocluster coated with a metal-phenol formaldehyde network structure (AuNCs@PDA-Mn) for tumour Photothermal therapy and chemodynamic therapy (PTT and CDT), which induces systemic immune responses to suppress tumour metastasis. Experimental results show that after continuous irradiation for 10 min under an 808 nm laser (1.0W/cm2), AuNCs@PDA-Mn not only exhibits better tumour inhibition both in vitro and in vivo but also triggers stronger immune effects systemically. Therefore, this combined PTT and CDT treatment approach has great potential and provides a clinically relevant and valuable option for triple-negative breast cancer.